Práticas pedagógicas de docentes da educação básica no ensino remoto: ciberespaço e multiletramento - Santos, Maria Porcina de Macedo (2022)
In times of a pandemic, new digital tools could be problematized and discussed by teachers in order to adapt and think of them as a didactic means, reorganizing and redirecting the teaching-learning process. In this context, this research aims to analyze pedagogical practices carried out by teachers in the context of cyberspace. These practices were adopted by education professionals who work in the formative itinerary of Languages and their Technologies in a state public school in Paraíba during emergency remote teaching. This study has a qualitative nature, whose methodological course was outlined by the phenomenological method presented by Husserl (1975; 1990; 2006), having as locus a Technical Integral Citizen School of High School located in the state of Paraíba. The technique used for data collection was the interview, using the semi-structured script as an instrument. The research subjects are the teachers of the training itinerary of Languages and their Technologies of that school. As a complementary technique, it was applied documental analyses. The methodology was guided by the theory of Bardin (2011; 2016) through the prism of categorical thematic analysis. In this direction, we seek a theoretical apparatus on cyberspace from the studies of Pierre Levy (1999; 2000; 2077; 2009; 2010) and the works on multiliteracy by Roxane Rojo (2012; 2013). We will discuss Modern Pedagogical Practices in the light of Franco (2015), Sacristán (1999), and Libâneo (2005); Regarding language practices, training itineraries, and general competencies, we will use the BNCC document (2017; 2018) to guide us. After a brief discussion about emergency remote teaching and the new learning spaces, we expose the field research. It is divided into sections that refer to the three forms of phenomenological description - noema, noesis, and eidetic variation, to then begin to analyze the analytical categories and empirical with a careful look, enriching the research with theories that are relevant for a better understanding of our object. Based on the analysis of the categories presented, it is evident that the emergency of remote teaching had some points that were satisfactory for teaching practice. But in some situations, social inequality and the lack of digital inclusion of the students caused negative impacts on the learning process concerning reading, writing, knowledge of the world, production, and textual interpretation. The teachers already observed these difficulties during the return to classes in the hybrid modality.